2018
DOI: 10.1039/c8cp03016b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of nanoparticles as a function of their spatial distribution on liposomes and cells

Abstract: The aggregation processes of magnetic nanoparticles in biosystems are analysed by comparing the magnetic properties of three systems with different spatial distributions of the nanoparticles. The first one is iron oxide nanoparticles (NPs) of 14 nm synthesized by coprecipitation with two coatings, (3-aminopropyl)trimethoxysilane (APS) and dimercaptosuccinic acid (DMSA). The second one is liposomes with encapsulated nanoparticles, which have different configurations depending on the NP coating (NPs attached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
3
10
0
1
Order By: Relevance
“…Our results suggest that MNPs heating capacity was reduced when associated to cells compared to their performance in water, indicating that the contact of MNPs with cells may affect their heating capacity, probably due to nanoparticle aggregation. According to our results, MNP aggregation seems to be independent of the cell type, incubation time or nanoparticle coating, supporting the idea that contact with cells is sufficient to induce nanoparticle aggregation, as previously proposed [39][40][41][42][43][44] . MNP aggregation in a non-controlled way could be one of the causes of the different magnetic behavior observed in cell-induced aggregation, and could explain the inefficient response to de AMF and reduced heating capacity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that MNPs heating capacity was reduced when associated to cells compared to their performance in water, indicating that the contact of MNPs with cells may affect their heating capacity, probably due to nanoparticle aggregation. According to our results, MNP aggregation seems to be independent of the cell type, incubation time or nanoparticle coating, supporting the idea that contact with cells is sufficient to induce nanoparticle aggregation, as previously proposed [39][40][41][42][43][44] . MNP aggregation in a non-controlled way could be one of the causes of the different magnetic behavior observed in cell-induced aggregation, and could explain the inefficient response to de AMF and reduced heating capacity.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been observed that the application of an AMF increases the generation of ROS by SPIONs both in suspensions 37 and within cells 38 , suggesting that in response to AMF application, SPIONs convert the energy they absorb into heat, enhancing ROS generation at their surfaces 32 . However, in the last years a number of studies [39][40][41][42][43] , indicate that the heating capacity of SPIONs is largely reduced when internalized by cells, due to increased viscosity of the environment, nanoparticle aggregation and dipolar interactions between particles (as previously observed by our group 44 ), which would justify the reduction of mechanical and thermal effects of SPIONs when subjected to an AMF. These contradictory observations make it rather difficult to draw general conclusions, partly because these studies were conducted using different nanoparticle types, concentrations, AMF amplitudes, frequencies, and cancer cell lines.…”
Section: Introductionsupporting
confidence: 60%
“…In another study, three systems with MNPs different spatial distributions and grades of aggregation were analyzed in order to compare their magnetic properties: isolated MNPs, MNPs-liposomes system, and MNPs-cell interaction (using, in turn, Jurkat cell line that attached MNPs to the outer membrane and Pan02 cell line that internalized the MNPs). Results showed that the biological environment played a crucial role in the dynamic magnetic response of the MNPs, being more altered for MNPs-cell system, and concluding that the simple fact of being in contact with the cells triggers MNPs aggregation [ 154 ].…”
Section: Mnp Behaviour In Response To Amf In the Biological Milieumentioning
confidence: 99%
“…880120), was further added (8% molar ratio) to the lipid mixture during lipid film preparation. The lipid/NP ratio was fixed to around 10,000 lipids per nanoparticle to minimize the amount of free particles [32,33]. Samples were further extruded via 200 and 100 nm polycarbonate filters (Whatman) to obtain a uniform magnetoliposome aqueous dispersion (Avanti Mini Extruder, Avanti Polar Lipids).…”
Section: Preparation Of Bmls and Oxa-bmlsmentioning
confidence: 99%